2018
DOI: 10.5552/drind.2018.1826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dynamic Contact Angle of Loose and Tight Sides of Thermally Compressed Birch Veneer

Abstract: Rotary-cut veneer is characterised by two sides, namely loose and tight surface, which have different properties. The information concerning dynamic contact angle behaviour of veneer sides plays an important role in effi cient use of veneer. Therefore, the objective of this study was to investigate the infl uence of different compression temperatures and pressures on various wetting behaviour of loose and tight sides of birch veneer. Veneer sheets were compressed in a hot press at temperatures of 150 and 180 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The work [ 59 ] reports a significant increase in hydrophobicity of a heat-treated beech wood surface at 200 °C, which was reflected in contact angle values bigger than 90°. Worsened wetting of heat-treated modified beech wood was also observed by other authors [ 60 , 61 ].…”
Section: Resultssupporting
confidence: 80%
“…The work [ 59 ] reports a significant increase in hydrophobicity of a heat-treated beech wood surface at 200 °C, which was reflected in contact angle values bigger than 90°. Worsened wetting of heat-treated modified beech wood was also observed by other authors [ 60 , 61 ].…”
Section: Resultssupporting
confidence: 80%
“…Numerous studies have reported that the surface wettability of thermally treated wood is reduced due to degradation of hygroscopic components (especially hemicellulose) (Hakkou et al 2005;Esteves et al 2007;Kocaefe et al 2008;Candan et al 2012;Bakar et al 2013;Chu et al 2016;Gérardin 2016). The compression temperature increase causes an increase in the contact angle, which is consistent with findings of previous studies (Diouf et al 2011;Ünsal et al 2011;Bekhta and Krystofiak 2016;Bekhta et al 2018). After the densification processes, depending on the compression ratio and temperature, the contact angle of untreated, paraffin, linseed oil, and styrene-impregnated specimens increased up to 23%, 56%, 46%, and 71% for aspen wood, and up to 24%, 42%, 51%, and 68% for fir wood, respectively.…”
Section: Fig 2 Roughness Values Of Impregnated and Densified Wood Spe...supporting
confidence: 90%
“…Adhesive quality is a critical component that must be meticulously evaluated during the production of laminated timber products [ 1 ]. In the manufacturing of wood products, surface preparation is a critical step preceding the gluing or finishing procedures [ 2 , 3 , 4 , 5 ]. Sanding is a method that is frequently employed in this process.…”
Section: Introductionmentioning
confidence: 99%